Thinking about police data: Analysts' perceptions of data quality in Canadian policing. (December 2022) - O'Connor, Christopher D; Ng, John; Hill, Dallas; Frederick, Tyler
Policing is increasingly being shaped by data collection and analysis. However, we still know little about the quality of the data police services acquire and utilize. Drawing on a survey of analysts from across Canada, this article examines several data collection, analysis, and quality issues. We argue that as we move towards an era of big data policing it is imperative that police services pay more attention to the quality of the data they collect. We conclude by discussing the implications of ignoring data quality issues and the need to develop a more robust research culture in policing.